Detection of Oxytetracycline Using an Electrochemical Label-Free Aptamer-Based Biosensor - Sanaz Akbarzadeh; Habibollah Khajehsharifi; Saeedeh Hajihosseini (Biosensors, 2022)
One of the most effective ways to detect and measure antibiotics is to detect their biomarkers. The best biomarker for the control and detection of oxytetracycline (OTC) is the OTC-specific aptamer. In this study, a novel, rapid, and label-free aptamer-based electrochemical biosensor (electrochemical aptasensor) was designed for OTC determination based on a newly synthesized nanocomposite including multi-walled carbon nanotubes (MWCNTs), gold nanoparticles (AuNPs), reduced graphene oxide (rGO), and chitosan (CS), as well as nanosheets to modify a glassy carbon electrode, which extremely enhanced electrical conductivity and increased the electrode surface to bind well with the amine-terminated OTC-specific aptamer through self-assembly. The (MWCNTs-AuNPs/CS-AuNPs/rGO-AuNPs) nanocomposite modified electrode was synthesized using a layer- by-layer modification method which had the highest efficiency for better aptamer stabilization. Differential pulse voltammetry (DPV), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and scanning electron microscopy (SEM) techniques were used to investigate and evaluate the electrochemical properties and importance of the synthesized nanocomposite in different steps. The designed aptasensor was very sensitive for measuring the OTC content of milk samples, and the results were compared with those of our previously published paper. Based on the calibration curve, the detection limit was 30.0 pM, and the linear range was 1.00–540 nM for OTC. The repeatability and reproducibility of the aptasensor were obtained for 10.0 nM of OTC with a relative standard deviation (RSD%) of 2.39% and 4.01%, respectively, which were not affected by the coexistence of similar derivatives. The measurement in real samples with the recovery range of 93.5% to 98.76% shows that this aptasensor with a low detection limit and wide linear range can be a good tool for detecting OTC.